Aminopeptidase N/CD13 as a potential therapeutic target in malignant pleural mesothelioma. Issue 5 (24th May 2018) - Otsuki, Takahiko; Nakashima, Taku; Hamada, Hironobu; Takayama, Yusuke; Akita, Shin; Masuda, Takeshi; Horimasu, Yasushi; Miyamoto, Shintaro; Iwamoto, Hiroshi; Fujitaka, Kazunori; Miyata, Yoshihiro; Miyake, Masayuki; et al.
Angiogenesis is a crucial factor in the progression of malignant pleural mesothelioma (MPM) and antiangiogenic strategies might be effective against MPM. Aminopeptidase N (APN)/CD13 promotes tumour angiogenesis and is associated with poor prognosis; however, its clinical significance in MPM remains unclear. In 37 consecutive patients with surgically resected MPM, we evaluated the association between immunohistochemical APN/CD13 expression in resected tumours and survival. Additionally, the antitumour and antiangiogenic effects of MT95-4, a fully humanised anti-APN/CD13 monoclonal antibody, were evaluated in mice orthotopically implanted with EHMES-10 (abundantly expressing APN/CD13) and MSTO-211H (scarcely expressing APN/CD13) MPM cells. High tumour APN/CD13 expression was associated with poor prognosis in MPM patients (p=0.04), and MT95-4 treatment reduced tumour growth and angiogenesis in mice harbouring EHMES-10 but not MSTO-211H cells. Furthermore, in mice harbouring EHMES-10 cells, MT95-4 combined with cisplatin more effectively suppressed tumour progression than cisplatin alone. Taken together, these results suggest that APN/CD13 is implicated in the aggressiveness of MPM. Here, MT95-4 treatment reduced tumour progression likely by inhibiting angiogenesis, suggesting APN/CD13 as a potential molecular target for MPM treatment. Additionally, combination treatment with MT95-4 and cisplatin could represent a promising approach to treating MPM exhibiting high APN/CD13 expression. Aminopeptidase N (APN)/CD13 is a potential therapeutic target in mesothelioma exhibiting high APN/CD13 expression http://ow.ly/dzmu30iGKzd